AN ANALYSIS OF THE RELATIONSHIP BETWEEN PERCEIVED TEACHER SUPPORT AND MOTIVATIONAL/EMOTIONAL RESPONSES - Murad Sherzad Othman; Mehmet Kılıç (Informascope, 2018)
Teacher support has an important role in effective language learning, because it helps students have successful motivational and emotional responses. It leads to decreases in anxiety and increases in intrinsic motivation, help-seeking behavior, and effort, factors of productive language learning. Based on this fact, the current study aims to analyze the relationships between EFL students' perceptions of emotional/instrumental support and their motivational/emotional responses. The participants were 200 EFL learners at a state university in Turkey. The data were collected through a questionnaire and a semi-structured interview. Correlation coefficients were obtained to detect the relationships of emotional/instrumental support with anxiety, intrinsic motivation, help-seeking behavior, and effort. Finally, independent-samples t-tests were administered to find potential differences between genders concerning emotional/instrumental support, anxiety, intrinsic motivation, help-seeking behavior, and effort. The findings showed that emotional and instrumental support are two related types of teacher support. Besides, significant positive correlations of emotional/instrumental support with intrinsic motivation, help-seeking behavior, and effort were detected, along with negative correlations of emotional/instrumental support with anxiety. Furthermore, the results showed no significant difference between genders concerning emotional support, anxiety, intrinsic motivation, and effort, but significant differences concerning instrumental support and help-seeking behavior were obtained based on gender. Moreover, the findings of the interviews supported those of the quantitative analyses.